The Transformative Impact of AI in Forensic Medicine: Innovations, Chal lenges, and Ethical Implications (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Artificial Intelligence (AI) is revolutionizing forensic medicine by enhancing the  accuracy, efficiency, and scope of criminal investigations and victim identification.  AI technologies, such as image and pattern recognition, DNA analysis, and predictive  analytics, offer unique opportunities to improve forensic practices. However, the  integration of AI into forensic medicine presents significant challenges, including  technological implementation, data security, infrastructure needs, and training of  professionals. Furthermore, ethical implications surrounding privacy, accountability,  bias, consent, and human rights are central to the responsible use of AI in forensic  contexts. The collection of sensitive personal data and the potential for AI to  influence critical legal decisions raises concerns about transparency, fairness, and  the protection of individual rights. To ensure the responsible application of AI in  forensic medicine, it is essential to develop comprehensive guidelines, regulations,  and ethical frameworks. As AI technology evolves, balancing innovation with  ethical considerations will be crucial. Future progress in AI in forensic medicine  will require ongoing collaboration between forensic scientists, AI researchers,  legal professionals, and policymakers. By addressing these challenges and ethical  dilemmas, the integration of AI can significantly enhance justice, public safety, and  victim closure, while maintaining the integrity of the justice system. Ultimately, the  successful integration of AI into forensic practices depends on caution, foresight, and  a commitment to ethical principles to safeguard both technological advancements  and fundamental human rights.
Keywords: Artificial Intelligence; forensic medicine; ethics; criminal investigations; data security